1991
DOI: 10.1104/pp.97.2.811
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sucrose-Sucrose-Fructosyltransferase in Barley Leaves

Abstract: The activity of sucrose-sucrose-fructosyltransferase (SST), a vacuolar enzyme strongly induced by light in excised leaves of barley (Hordeum vulgare L.), rapidly declined even in continuous light upon feeding of cycloheximide (CHI). The rate of decline was similar to that observed in light-treated leaves that were placed into darkness, in the presence or absence of CHI. The protease inhibitor leupeptin totally stopped the decline in SST activity in the dark and caused a substantial increase in the rate of indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Based on this fact and on detailed work with barley leaves (Wagner et al, 1983;Wagner and Wiemken, 1987;Obenland et al, 1991), our group previously suggested SST to be the key enzyme for fructan accumulation in the grasses also, and we reported the partia1 purification of two SST activities from barley protoplasts, one producing 1 -kestose and the other 6-kestose (Wagner and Wiemken, 1987). However, these studies were subject to recent criticism (Cairns et al, 1989;Cairns and Ashton, 1991;Pollock and Cairns, 1991;Winters et al, 1992), which focused on two main points.…”
mentioning
confidence: 89%
“…Based on this fact and on detailed work with barley leaves (Wagner et al, 1983;Wagner and Wiemken, 1987;Obenland et al, 1991), our group previously suggested SST to be the key enzyme for fructan accumulation in the grasses also, and we reported the partia1 purification of two SST activities from barley protoplasts, one producing 1 -kestose and the other 6-kestose (Wagner and Wiemken, 1987). However, these studies were subject to recent criticism (Cairns et al, 1989;Cairns and Ashton, 1991;Pollock and Cairns, 1991;Winters et al, 1992), which focused on two main points.…”
mentioning
confidence: 89%
“…During periods of fructan accumulation, SST activity increases Cairns & Pollock, 19886;Smouter & Simpson, 19916;Obenland et al, 1991) and the evidence indicates that FEH activity in some grasses may be reduced significantly. The concentration of sucrose in leaves and shoots of Lolium spp.…”
Section: Fruct\n Turnovermentioning
confidence: 99%
“…Although FEH activities in tissues from both seedlings and reproductive plants of L. rigidum are similar, rates of invertase activity vary considerably, being highest in young tissues and lowest in mature plant parts (Bonnett & Simpson, 1993). If the shoot tissues of grasses have been induced to accumulate fructans, the activity of sucrose-sucrose fructosyl transferase (SST) is induced to relatively high levels (Wagner, W'iemken & Matile, 1986;Cairns & Pollock, 19886;Obenland et al, 1991) and SST and FEH may be present simultaneously Smouter & Simpson, 1991 b). This situation does not occur in specialized storage organs of some species because SST and FEH are not active at the same time.…”
Section: Occurrence and Localization Of Fehmentioning
confidence: 99%
“…Its accumulation triggers the onset of fructan synthesis, it provides the substrate for polymerization (Cairns & Pollock, 1991) and there is evidence that it stabilizes the enzyme(s) of fructan synthesis against proteolytic degradation, a proposed feature of the metabolic control of fructan metabolism (Obenland et al, 1991, Cairns & Ashton, 1994. The presence of sucrose in vitro stabilizes small fructans against hydrolysis and is crucial to their accumulation.…”
Section: Physiological Significancementioning
confidence: 99%